Conceptual design of a virtual pick and place operation using an articulated robot arms: article / Siti Fatimah Mahmud - Mahmud, Siti Fatimah (2012)
With the development of rising technology every year, automation and robotics is essential to meet the needs of modern life. Nowadays, the technology of virtual design is considered as one of the most important thing for the process of overall design in engineering. In this paper, an articulated robot arms was virtually design for a virtual pick and place operations. 3D-CAD system software has been used. SolidWorks software has been introduced. In this project, each of every part of the robot and whole system has been created. Then, all of it has simulated in the software. Motion and force has created to make an appropriate system. The six axes articulated robot arms was created which using a concept of industrial automation robot. Simulation results of the articulated robot arms are presented to demonstrate the assembly robot in the system.